2003
DOI: 10.1303/aez.2003.7
|View full text |Cite
|
Sign up to set email alerts
|

Life-history traits of the Kanzawa spider mite Tetranychus kanzawai (Acari: Tetranychidae).

Abstract: Performance of phytophagous insects and spider mites on different host plants is influenced by the nutritional value and defenses of the plants; important factors include secondary chemicals, leaf nutrition, leaf age and leaf surface structure (Gerson and Aronowitz, 1980; Jaenike, 1990;Wilson, 1994;Van Impe and Hance, 1993; Krips et al., 1998;Agrawal, 2000). When spider mites infest chemically defended or poor-quality plants, their intrinsic rate of natural increase (r m ) should be low (Gould, 1979;Fry, 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
2
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 26 publications
5
32
2
3
Order By: Relevance
“…Then fecundity of females was checked and laid eggs were counted and removed daily from each leaf disc. This experiment was continued until all experimental females died (Gotoh and Gomi 2003). We evaluated fecundity of 16 two-spotted mite females for each cultivar.…”
Section: Methodsmentioning
confidence: 99%
“…Then fecundity of females was checked and laid eggs were counted and removed daily from each leaf disc. This experiment was continued until all experimental females died (Gotoh and Gomi 2003). We evaluated fecundity of 16 two-spotted mite females for each cultivar.…”
Section: Methodsmentioning
confidence: 99%
“…Of these species, four (T. kanzawai, T. ludeni, T. piercei and T. urticae) are known to be pests of agricultural crops (Bolland et al, 1998). T. parakanzawai is polyphagous (Gomi and Gotoh, 1996) and has a high r m value (0.276 at 25°C; Species composition and seasonal changes of spider mite density on a leguminous plant Pueraria lobata Gotoh and Gomi, 2003). T. pueraricola is also polyphagous but prefers leguminous plants (Gotoh et al, 2004a), and has a high r m value (0.299 at 25°C; Gotoh et al, 2004b); therefore, T. parakanzawai and T. pueraricola have potential as pests when they invade a crop field.…”
Section: Introductionmentioning
confidence: 99%
“…During the screening tests, oil pressed out of seeds of sugar apple (Annona squamosa) was found to be very effective in causing mortality of silverleaf whitefly nymphs, while its aqueous extract was ineffective and the ethanolic extract was only slightly effective. Since the cotton aphid, Aphis gossypii Glover (Conway et al 2003), and the Kanzawa spider mite, Tetranychus kanzawai Kishida (Gotoh & Gomi 2003), are also important pests of many agricultural crops and pesticides have been frequently applied for their control, they were also tested. It was found that oil from sugar apple seeds was also very effective in reducing the survival rate of these two pests.…”
mentioning
confidence: 99%